Cole Steele adventure comics - Bradford, Royce (Sydney : Wollumbin Press, 1950)
Cole Steele is a secret agent of the Criminal Investigation Bureau. His true identity is known to the Commissioner of Police alone. At all times he assumes the role of a notorious criminal to help him in his investigations.
Cover title.
Description based on: No. 3.
Keywords: Spies -- Comic books, strips, etc; Spies -- Periodicals; Undercover operations -- Comic books, strips, etc; Undercover operations -- Periodicals; Australian; Comics (Graphic works)